2016
DOI: 10.1111/ecc.12607
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of sexual functioning in the early weeks of breast cancer treatment

Abstract: This study describes women's sexual functioning in the early weeks of breast cancer treatment and the possible sexual changes that women may experience compared with pre-treatment functioning. Seventy-five patients filled out a questionnaire on sexual functioning and participated in a semi-structured interview on changes in sexual life and intimacy after treatment. Sixty-two women were sexually active before treatment; three post-treatment patterns of sexual behaviour were identified: 22.6% of these women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
1
8
0
1
Order By: Relevance
“…After cancer, the majority of women in this study (70.2%) confirmed that they continued to have sexual activity, with is consistent with the literature [14, 15, 16]. Although the frequency of sexual relations is lower after cancer, 60.7% reported that they have sexual relationships 1–2 times per month [5, 9, 12, 16].…”
Section: Discussionsupporting
confidence: 90%
“…After cancer, the majority of women in this study (70.2%) confirmed that they continued to have sexual activity, with is consistent with the literature [14, 15, 16]. Although the frequency of sexual relations is lower after cancer, 60.7% reported that they have sexual relationships 1–2 times per month [5, 9, 12, 16].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, association between the loss of sexual desire and satisfaction with mastectomy due to BC was depicted by Turkish women with BC through a cross-sectional study by Özturk and Akyolcu [ 30 ]. Cairo Notari et al, in a qualitative study of the French women's experiences of sexual functioning in the early weeks of BC treatments showed that most women experienced a lack of sexual desire [ 31 ]. Moreover, the results of a systematic review demonstrated that women with BC experienced some degrees of sexual issues including decreased sexual arousal, orgasm, libido, and sexual pleasure [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Negative emotional effects, including depression and anxiety, have also been associated with these changes. 13 It is noteworthy that, despite major sexual changes, the impact of these changes on the quality of patients’ relationships may vary: Some women report persistent sexual problems that lead to complicated sexual activities and marital conflict, 14 , 15 , 16 , 17 while a few describe positive increases in non-intercourse intimacy and manage to restore satisfactory sexual relationships after their diagnoses. 7 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%